2019
DOI: 10.1115/1.4042387
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Method Evaluating Control Actions in STPA-Based Model of Ship-Ship Collision Avoidance Process

Abstract: As system-theoretic methods of safety assessment are developed, certain aspects of them remain under-explored, including the question of prioritizing one control action's adequacy over another. This paper investigates this feature based on the analysis of a process of merchant vessels' collision avoidance. We first elicit experts' views on the structure of the process and importance of particular interactions occurring therein. Thence, we analyze a number of incident reports to examine the percentage of cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…With this underlying principle, STPA is capable of analyzing the hazards of unsafe interactions (controls and feedbacks), as well as component failures (execution of control actions) [65]. STPA has been widely used in various industries and sectors such as aviation, aerospace, defense, nuclear power plants, oil and gas industries, automobiles, cybersecurity, and so on, and this method has been gaining interest and application in the maritime domain recently [66], especially for the hazard analysis of autonomous ships. For instance, Wróbel et al [67] applied STPA to develop and analyze a preliminary model of autonomous ships.…”
Section: Hazard Analysis For Massmentioning
confidence: 99%
“…With this underlying principle, STPA is capable of analyzing the hazards of unsafe interactions (controls and feedbacks), as well as component failures (execution of control actions) [65]. STPA has been widely used in various industries and sectors such as aviation, aerospace, defense, nuclear power plants, oil and gas industries, automobiles, cybersecurity, and so on, and this method has been gaining interest and application in the maritime domain recently [66], especially for the hazard analysis of autonomous ships. For instance, Wróbel et al [67] applied STPA to develop and analyze a preliminary model of autonomous ships.…”
Section: Hazard Analysis For Massmentioning
confidence: 99%
“…STPA has already been criticized for being a qualitative approach that does not consider risk quantification (Abaei et al, 2021;Ramos et al, 2020). To prioritize the control actions resulting from the STPA analysis, Gil et al (2019) suggested evaluating the unsafe control actions identified by STPA based on the historical ship accident data. The authors highlighted that more research should be conducted to define a structured control action prioritization technique.…”
Section: Introductionmentioning
confidence: 99%
“…The Bayesian Network (BN) is a graphical technique expressing complex probabilistic relationships, especially in nonprecise information estimates prone to uncertainty [31,32], it is widely used in the probabilistic occurrence estimation and quantitative risk assessment of maritime accidents or incidents [33][34][35][36][37][38][39]. The BN can be incorporated with systematic approaches for processing the evolution, dynamic variation, and complex dependencies of maritime accidents, such as Accident Map (AcciMap) [34], System Theoretic Process Analysis (STPA) [40,41], and Functional Resonance Analysis Method (FRAM) [28,42]. Moreover, a Dynamic Bayesian Network (DBN) is an improved technique for modeling a time series or dynamic process by expanding BNs [43][44][45].…”
Section: Introductionmentioning
confidence: 99%